The Effectiveness of Home-Based Training Software Designed to Influence Strategic Navigation Preferences in Healthy Subjects - van der Kuil, Milan N. A.; Evers, Andrea W. M.; Visser-Meily, Johanna M. A.; van der Ham, Ineke J. M. (Frontiers in Human Neuroscience, 2020)
Patients with acquired brain injuries often report navigation impairments. Impairments are often restricted to spatial abilities related to a particular frame of reference: egocentric (self-based) or allocentric (object-based). We have developed a rehabilitation training designed for patients to adopt either an egocentric or an allocentric compensatory navigation strategy. The training consists of a psychoeducation session and a software package that includes allocentric or egocentric navigation exercises in virtual environments. The aim of the current study was to test the key assumption that strategic preference can be changed by using a navigation training in healthy participants (n=82). Strategic navigation preference, objective and self-reported spatial abilities were assessed in pre- and post-training sessions. Based on their pre-training strategic preference, participants received either the egocentric training (n = 19) or the allocentric training (n = 21) version of the training. These participants engaged in 4 training sessions over a period of 2–3 weeks. A second group of participants did not use the training software (n = 43) and served as a control group. Results show that 50% of participants that received the egocentric training shifted from an allocentric to and an egocentric strategic preference. The proportion of participants that switched their strategic preference as a result of the allocentric training was identical to this proportion in the control group (19%).The training did not affect objective and self-reported navigation abilities as measured in the pre- and post-training session. We conclude that strategic navigation preferences can be influenced by using a home-based training in healthy participants. However, using the current approach, only a preference shift from an allocentric to an egocentric navigation strategy could be achieved. The effectiveness of this navigation strategy training should next be assessed in relevant patient populations.